On a class of variational-type inequalities involving curvilinear integral functionals. (16th December 2022) - Treanţă, Savin; Singh, Shipra; Jayswal, Anurag
Abstract : In this paper, weak sharp solutions are investigated for a class of variational-type inequalities involving curvilinear integral functionals. Moreover, by using the minimum principle sufficiency property, some characterization results on the weak sharpness property of the solution set for the considered class of variational-type inequalities are formulated and proved. Finally, in order to illustrate the main results, an application is provided.